Birds in estuaries can act as indicators of climate change: a study at a key wintering site for waterbirds in Europe - Marchowski, Dominik; Jankowiak, Łukasz; Wysocki, Dariusz; Ławicki, Łukasz; Girjatowicz, Józef (PeerJ Preprints, 2016)
Climate change can shift the winter range of many species and birds can act as indicators of this process. Estuaries of large rivers are places where different waterbirds winter with each species reflecting their own behavior and sensitivity to weather changes. Knowing these behaviors and tracking long-term changes in the number of birds, we can confirm the direction of climate change. One estuary of key importance for wintering waterfowl is the Odra River Estuary situated in the south-western part of the Baltic Sea. The most numerous birds here belong to two groups: benthic feeders and fish feeders. We show that numbers of all benthivorous waterbirds were negatively correlated with the presence of ice, but for piscivorous there was no relationship. We anticipate that with continued global warming the importance of this area for benthic feeders will increase, but will decrease for fish feeders. Among the seven species of benthivorous birds we studied, one showed an increase in numbers (Greater Scaup Aythya marila), two were stable (Tufted Duck A. fuligula and Eurasian Coot Fulica atra) and two decreased (Common Pochard A. ferina and Common Goldeneye Bucephala clangula); among the piscivorous group two species (Smew Mergellus albellus and Goosander Mergus merganser) showed a decline. The decline of the Common Pochard may reflect that species global decline. Climate change may be responsible for some of the local changes in the study area, namely the increase in the number of Greater Scaup and reduction in the numbers of Common Goldeneye, Smew and Goosander.
Keywords: winter range shift; ice coverage sensitivity; Greater Scaup; Common Pochard; Tufted Duck; Eurasian Coot; Smew; important bird areas; behavior; Baltic Sea